2020
DOI: 10.1103/physrevb.101.115120
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of hinge states in second-order topological insulators via the cutting procedure

Abstract: In recent years, second-order topological insulators have been proposed as a new class of topological insulators. Second-order topological insulators are materials with gapped bulk and surfaces, but with topologically protected gapless states at the intersection of two surfaces. These gapless states are called hinge states. In this paper, we give a general proof that any insulators with inversion symmetry and gapped surface in class A always have hinge states when the Z4 topological index µ1 is µ1 = 2. We cons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…We note that, in this paper, we consider a process of cutting the three-dimensional HOTI along a plane. In another paper, we consider a process of cutting the threedimensional HOTI along two planes 43 . In the paper, we discuss allowed positions of the hinge states, which is determined only if we consider a cutting along two planes.…”
Section: Introductionmentioning
confidence: 99%
“…We note that, in this paper, we consider a process of cutting the three-dimensional HOTI along a plane. In another paper, we consider a process of cutting the threedimensional HOTI along two planes 43 . In the paper, we discuss allowed positions of the hinge states, which is determined only if we consider a cutting along two planes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that some topological crystalline insulators exhibit higher-order bulk boundary correspondence, which are known as higher-order topological insulators . For example, three-dimensional second-order topological insulators with inversion symmetry (and time-reversal symmetry) have protected anomalous gapless mode along the hinges 9,[12][13][14]16,[21][22][23] , and two-dimensional second-order topological insulators with rotation symmetry have protected quantized corner charges [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] . Such fractionally quantized corner charges are generalizations of the quantized surface charge caused by the quantized bulk electric polarization 43 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the notion of conventional TI's is generalized to higher order topological insulators (HOTI) with n > 1 [32][33][34][35][36][37][38][39][40][41][42][43]. The HOTI's are protected by the crystalline (spatial) symmetries such as the inversion, the mirror reflection, and the four fold rotation or space-time symmetries of both the bulk and the boundaries [32][33][34][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%